2018
DOI: 10.3389/fimmu.2018.01460
|View full text |Cite
|
Sign up to set email alerts
|

Deterioration of Organ Function As a Hallmark in Sepsis: The Cellular Perspective

Abstract: Development of organ dysfunction discriminates sepsis from uncomplicated infection. The paradigm shift implicated by the new sepsis-3 definition holds that initial impairment of any organ can pave the way for multiple organ dysfunction and death. Moreover, the role of the systemic inflammatory response, central element in previous sepsis definitions, has been questioned. Most strikingly, a so far largely underestimated defense mechanism of the host, i.e., “disease tolerance,” which aims at maintaining host vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 61 publications
0
24
0
Order By: Relevance
“…Thus a positive fluid balance may be epiphenomenal rather than necessarily causative of a higher mortality. Furthermore, changes in a blood mediator level linked to a poor outcome can be part of the host response to injury, or even a protective element related to disease tolerance (Medzhitov et al , ; Bauer et al , ).…”
Section: Sepsis: a New Who Global Health Prioritymentioning
confidence: 99%
“…Thus a positive fluid balance may be epiphenomenal rather than necessarily causative of a higher mortality. Furthermore, changes in a blood mediator level linked to a poor outcome can be part of the host response to injury, or even a protective element related to disease tolerance (Medzhitov et al , ; Bauer et al , ).…”
Section: Sepsis: a New Who Global Health Prioritymentioning
confidence: 99%
“…It becomes apparent in all these studies that metabolic processes are closely interlinked to damage and repair processes in cells and tissues [5]. The homeostasis of synthesis and formation of cellular organelles on one site and their degradation is an essential prerequisite for vitality of the cells and, thus, integrity of tissue and organs.…”
Section: Metabolic Reflections Of Resistance and Tolerance Responsesmentioning
confidence: 99%
“…It is now well-established that activation of TLR4 is one of the two innate immune pathways triggered during Gram-negative bacterial sepsis in immunocompromised patients (the other one is caspase 11 activation in macrophages) (5,6). Sepsis is defined as a lifethreatening condition that leads to circulatory abnormalities, organ dysfunction, and death due to the overwhelming response of the body's immune system to bloodstream infection (7,8). Recently, a few studies have demonstrated that the repetitive exposure of pathogen associated molecular patterns (PAMPs) such as LPS to innate immune cells can lead to a subsequent increase or decrease in their responsiveness termed as training or tolerance, respectively (9).…”
Section: Introductionmentioning
confidence: 99%